(untitled) (Canadian Journal of Native Studies, 2026)
This exploratory study examines ‘The Highway of Tears’ cases in Northern British Columbia. Qualitative interviews with local Indigenous Peoples and Elders on the Highway of Tears provide empirical data to inform the issue of Missing and Murdered Indigenous Women and Girls (MMIWG) in Canada. This research demonstrates the systemic and multi-faceted racism that continues to marginalize and oppress Indigenous Peoples. Such discrimination exists within Canadian society and the organizational structure of the Royal Canadian Mounted Police. This research uses organizational and environmental approaches to police deviance and interviews with First Nations to contribute to understanding why the MMIWG cases are under-investigated and remain unsolved.